Acute effect of single bout exercise modalities (open-skills vs closed-skills) on trail-making task in recreationally active older adults / Syed Murshid Syed Zubir ... [et al.]. - Syed Zubir, Syed Murshid; Raja Hussain, Raja Nurul Jannat; Linoby, Adam; Zulkhairi, Aqil; Mohd Dan, Azwa Suraya (2024)
This study investigates the cognitive benefits of acute exercise modalities in elderly individuals, focusing on engagement in badminton (open-skills) versus closed-skill (e.g., swimming, cycling and running) exercises, compared to sedentary activity. A total of 67 participants aged 60 and above were 16he16ious16s16 into three groups: badminton (open-skills) (BAD, n = 21), closed-skill exercise (CSP, n = 22), and a sedentary control (CON, n = 24) group. The study evaluated the cognitive impact of a single exercise bout on these tasks. Results revealed that participation in badminton exercises significantly improved executive function and working memory compared to closed-skill and passive activities. Specifically, in the N-Back Task, the BAD group showed a reaction time of 810.4 m/s and 75.2% accuracy, outperforming the CSP (reaction time: 826.2 m/s, accuracy: 70.8%) and CON groups (reaction time: 840.8 m/s, accuracy: 56.2%). Similarly, in the TMT-B, the BAD group (46.7 seconds) outperformed the CON group (64.0 seconds). Accurately, the BAD group showed notable cognitive enhancements post-exercise, particularly in working memory and executive functions. For instance, the BAD group improved in TMT-B from 46.7 seconds to 45.4 seconds post-exercise, while the CSP and CON groups did not exhibit similar improvements. These findings suggest that the type of physical activity plays a critical role in cognitive health, with badminton offering superior benefits. The study highlights the importance of exercise modality in cognitive function enhancement among the elderly, challenging the notion that all forms of physical activity are equally beneficial for cognitive health.